A global bioenergy supply network redesign through integrating transfer pricing under uncertain condition. (20th January 2019) - Razm, Sobhan; Nickel, Stefan; Saidi-mehrabad, Mohammad; Sahebi, Hadi
Abstract: Biomass, as a renewable material and a clean alternative fuel in generating electricity and heat, is of particular importance in the transportation industry for the production of biofuel instead of fossil fuels. So far, many models have been proposed for the Bioenergy Supply network design, all of which are local and focus on designing new configurations that conform to a specific country's economic policies. But since globalization of the economy and industry is unavoidable today, effort has been made in this paper to propose a global Bioenergy Supply network management model. Contrary to the present literature on the Bioenergy Supply network, the proposed model addresses the redesign of an existing biomass supply network through logistic decisions, financial problems, and related merits. The model objectives can help managers to make decisions using the best transfer prices to maximize the global after tax profit of the biomass company even under uncertain conditions. To validate the model, use has been made of the data of a case study in Iran and Armenia. At last, it is concluded when transfer price is considered at the model, the global after tax profit can increase more than 8% compared with the case of without transfer price. Graphical abstract: The structure of the global bioenergy supply network redesign (BE-SNR). Highlights: Developing an optimization model that redesigns a global bioenergy supply network (BE-SN). Integrating transfer pricing into the model as a variable. Considering world trade-specific parameters/incoterms. Presenting a non-deterministic model and its solution using stochastic programming. Applied the model to a case study in Iran and Armenia.